EFFECT OF ICT MEDIATED RECIPROCAL TEACHING ON ACHIEVEMENT IN MATHEMATICS - Nayak, R K; Sinha, Somnath (SCHOOL SCIENCE, 2025)
This pretest–post test equivalent groups experimental study compared a procedure that is the ICT Mediated Reciprocal Teaching (IMRT) for helping a section of Class IX students to be better able to improve the achievement in summative assessment conducted by school than a control group of Class IX students. It was predicted that IMRT would improve the achievement and facilitate both the gender equally. Comprehending mathematics word problems related to mensuration, algebra and Euclid geometry of Class IX was delivered using IMRT to two groups of Class IX students. The achievement of students in their last school conducted test was taken as pretest scores of both the groups. Comparing the estimated marginal means using ANCOVA showed that students in the experimental ICT mediated group (M = 39.7, SD = 24.4) scored better in post test than did the students in the control group (M = 40, SD = 28.6). These results suggest IMRT has significant impact on improving the achievement in mathematics. There was no significant difference on the mean test scores of girls and boys in any of the pretest and post test; which indicated gender had no effect on achievement in mathematics at Class IX level.